PEER INSTRUCTION METHOD IN IMPROVING STUDENTS SPEAKING ABILITY - Ali Wira Rahman; Dwi Retnowati Putri (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This research based on the students’ problem regarding to English teaching especially speaking ability. It was caused by the teaching method of the teacher in classroom was not interesting for students. The objective of the research was whether or not the use of Peer Instruction method was able to improve the speaking ability of the eleventh grade students at SMA Negeri 1 Watang Pulu. The research applied quasi-experimental design with two group namely experimental class and control class. The population of this research was the eleventh grade students at SMA Negeri 1 Watang Pulu in academic year 2016/2017. The sample was XI.IPA 1 as experimental class and XI.IPA 2 as control class. The result of the data analysis showed that the students’ speaking ability improved, it was showed by the mean score of pre-test was 41.13 and the post-test was 57.65. It showed that the speaking ability of the eleventh grade students at SMA Negeri 1 Watang Pulu improved through Peer Instruction method. In conclusion, teaching speaking through Peer Instruction method was effective to improve the eleventh grade students’ speaking ability at SMA Negeri 1 Watang Pulu of academic year 2016/2017.